1969
DOI: 10.1139/v69-165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the oxidation of formaldehyde by hexacyanoferrate(III) ion

Abstract: The kinetics of the reaction between formaldehyde and hexacyanoferrate(II1) ion in alkaline medium has been investigated at four temperatures. The data show that the reaction is rapid initially, then follows a simple first order rate with respect to each of the hexacyanoferrate(II1) ion, formaldehyde, and hydroxide ion. Calculations reveal that only 0.27 % of the formaldehyde corresponds to the initial rapid reaction; the remaining 99.73 % follows the kinetics described. The net rate of the oxidation of formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Tests to establish the formation of a free radical intermediate using vinyl acetate were negative. This is in agreement with previous ferricyanide oxidations of similar functional groups, where it is concluded that the free radical had no independent existence [7].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Tests to establish the formation of a free radical intermediate using vinyl acetate were negative. This is in agreement with previous ferricyanide oxidations of similar functional groups, where it is concluded that the free radical had no independent existence [7].…”
Section: Resultssupporting
confidence: 93%
“…Kinetic studies of the oxidation of formaldehyde (HCHO) with ferricyanide (Fe(CN) 6 3-) [7] and octacyanotungstate(V) (W(CN) 8 3-) [8] have been reported. In both studies, the reactions are first order with respect to the metal cyanide complex, formaldehyde and the hydroxide ion and correspond to the rate law:…”
Section: Introductionmentioning
confidence: 99%
“…1), by plotting −dc/dt values against [hexacyanoferrate(III)] (Fig. 2), by calculating the firstorder rate constant k 1 …”
Section: Resultsmentioning
confidence: 99%
“…Transition metals like osmium [1], iridium [2], tungsten [3], etc. have successfully been used as homogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…However, Speakman and Waters [3] have suggested different paths of oxidation of aldehydes, ketones and nitroparaffins. Singh and coworkers [4,5], while discussing the oxidations of formaldehyde, acetone and ethyl methyl ketone have suggested that the oxidation takes place via an electron transfer process resulting in the formation of a free radical intermediate.…”
Section: Introductionmentioning
confidence: 99%